2021
DOI: 10.7717/peerj.11772
|View full text |Cite
|
Sign up to set email alerts
|

Shape familiarity modulates preference for curvature in drawings of common-use objects

Abstract: Drawing is a way to represent common-use objects. The contour of an object is a salient feature that defines its identity. Preference for a contour (curved or angular) may depend on how familiar the resulting shape looks for that given object. In this research, we examined the influence of shape familiarity on preference for curved or sharp-angled drawings of common-use objects. We also examined the possibility that some individual differences modulated this preference. Preference for curvature was assessed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 93 publications
(149 reference statements)
5
19
1
Order By: Relevance
“…Even though recent research is targeting inter-individual differences in shape preferences in spaces and objects’ contexts, the role of individual measures on preference is as yet uncertain, requiring further investigations [ 33 , 84 ]. However, when looking closely at previous studies, an interesting sex effect appears.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though recent research is targeting inter-individual differences in shape preferences in spaces and objects’ contexts, the role of individual measures on preference is as yet uncertain, requiring further investigations [ 33 , 84 ]. However, when looking closely at previous studies, an interesting sex effect appears.…”
Section: Discussionmentioning
confidence: 99%
“…The same set of images showed a preference for curved interiors when the sample size consisted of more females than males [ 8 , 49 ]. The authors interpreted the preference for rectilinear spaces in their study as the result of familiarity, which was previously found to be relevant for preference formation [ 34 , 38 ], although other studies investigating drawings of familiar objects have found it to modulate preference for curvature [ 33 ]. The sex effect was also found when presenting sketches of familiar objects, where females judged curvilinear objects as more peaceful than males [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This final task asked participants to choose which of each pair of drawings they would prefer to draw and to indicate the strength of this preference on a scale (Park, Shimojo, & Shimojo, 2010;Williams et al, 2018). In Experiments 1 and 2, we expected that participants would prefer the curved drawings as shown by previous studies Chuquichambi et al, 2021). In Experiment 3, we expected that participants would prefer to draw the curved stimuli because of the relationship between aesthetic and drawing preference reported by Williams et al (2018).…”
Section: Purpose Of the Present Studymentioning
confidence: 99%